2015
DOI: 10.1136/gutjnl-2014-308988
|View full text |Cite
|
Sign up to set email alerts
|

Tumour-educated circulating monocytes are powerful candidate biomarkers for diagnosis and disease follow-up of colorectal cancer

Abstract: Our study is the first to demonstrate monocyte plasticity in response to tumour-released soluble factors. The identified distinct signature in tumour-educated monocytes might be used as a candidate biomarker in CRC diagnosis and harbours the potential for disease follow-up and therapeutic monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 29 publications
3
74
1
Order By: Relevance
“…A case-control study characterized peripheral blood monocyte samples from 360 CRC patients at four European oncology centers. Their results suggest that tumor-educated circulating monocytes could be used as a biomarker in CRC diagnosis, and potentially also for follow-up and therapeutic monitoring [23]. Furthermore, the presence of TAMs in the tumor stroma was correlated with poor survival in CRC patients, but the opposite correlation was found if TAMs were at the tumor front.…”
Section: Dual Role Of Tams In Crcmentioning
confidence: 99%
“…A case-control study characterized peripheral blood monocyte samples from 360 CRC patients at four European oncology centers. Their results suggest that tumor-educated circulating monocytes could be used as a biomarker in CRC diagnosis, and potentially also for follow-up and therapeutic monitoring [23]. Furthermore, the presence of TAMs in the tumor stroma was correlated with poor survival in CRC patients, but the opposite correlation was found if TAMs were at the tumor front.…”
Section: Dual Role Of Tams In Crcmentioning
confidence: 99%
“…For example, in patients with stage III colon cancer, a higher lymphocyte to monocyte ratio was associated with increased time to recurrence and overall survival . In colorectal cancer patients, peripheral blood monocytes display a gene signature that is not present in healthy monocytes or other types of cancer, highlighting the potential for cancer‐specific biomarkers based on monocyte signatures …”
Section: Targeting Of Monocytes For Cancer Diagnostics and Therapymentioning
confidence: 99%
“…115 In colorectal cancer patients, peripheral blood monocytes display a gene signature that is not present in healthy monocytes or other types of cancer, highlighting the potential for cancer-specific biomarkers based on monocyte signatures. 63 Discrimination of monocyte subsets may provide additional diagnostic power and biological insights given the divergent roles of different monocyte subsets in cancer progression. A lower frequency of peripheral blood CD14 + CD16monocytes was associated with their increase in bone marrow and greater survival in pancreatic cancer, 76 suggesting that pancreatic tumors systemically alter monocyte trafficking.…”
Section: Monocytes As Cancer Diagnosticsmentioning
confidence: 99%
“…Previous investigations have shown that some gene expressions in peripheral blood mononuclear cells (PBMCs) from breast cancer patients are correlated with circulating tumor cells, tumor grade and formation of metastasis . The changes of gene expression profiles in PBMCs, in response to factors released by cancer cells, are reversible and specific to tissue types of cancers such as prostate cancer, breast cancer, lung cancer and colorectal cancer . A recent study has demonstrated that the gene expression level of the calcium‐activated chloride channel (CaCC) ANO1 in PBMCs is highly correlated with tumor size and differentiation of gastrointestinal stromal tumors (GIST), whereas most patients with GIST become ANO1‐negative after surgery or decline of ANO1 expression level in response to imatinib treatment .…”
Section: Introductionmentioning
confidence: 99%